Influence of bilayer coating of salicylic acid and edible wax on chilling injury and functional attributes of guava. Issue 7 (17th May 2021) - Madhav, Janagam Venu; Sethi, Shruti; Sharma, Ram Roshan; Nagaraja, Arumugam; Arora, Ajay; Varghese, Eldho
Abstract: In the present investigation, the effect of bilayer coating was evaluated on the chilling injury and quality of guava fruits. The fruits of white fleshed guava cv. Allahabad Safeda and pink fleshed cv. Lalit were subjected to treatment with 5‐sulfosalicylic acid (2 mM) followed by vegetable wax (1:4 v/v). The treated fruits were stored under two temperatures, namely, 5 and 10°C for 15 days. Post cold storage, fruits were transferred to supermarket conditions (20 ± 2°C) for a 2‐day shelf life simulation period. The results revealed that treated fruits showed significantly lower weight loss and chilling injury compared to control fruits. The bilayer coating was effective in delaying yellowing of fruit skin and respiration peak with greater retention of total antioxidant capacity compared to control fruits. The treated fruits maintained the shelf life up to 12 + 2 days and 9 + 2°days under 5 and 10°C, respectively. Practical applications: We recommend that bilayer application of salicylic acid and edible wax can efficiently suppress chilling injury, extend shelf life, and maintain quality of guava under low temperature storage.